2021
DOI: 10.1590/1984-3143-ar2021-0002
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of dopperfluxometric indices of maternal-fetal structures in pregnant ewes

Abstract: The aim of this study was to evaluate the blood flow of the uterine artery, fetal aorta and umbilical artery in the physiological pregnancy of sheep by means of pulsed Doppler throughout the gestational period. Thirty Santa Inês ewes weighing between 45.4±4.3 kg and aged 2 to 5 years were selected. The evaluations were carried out weekly from the 3 rd to the 21 st gestational week. Peak systolic velocity (PSV), end diastolic velocity (EDV) and resistance index (RI) were obtained. Analysis of variance was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 27 publications
4
2
0
Order By: Relevance
“…In this study, the umbilical cord was visualized for the first time around the 33rd day of pregnancy, similar to that reported by other authors [ 4 ]. Rickard et al [ 26 ] visualized the umbilical cord already on the 23rd day of pregnancy, while Kumar et al [ 34 ] identified free movement of the umbilical cord on the 39th day of pregnancy.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In this study, the umbilical cord was visualized for the first time around the 33rd day of pregnancy, similar to that reported by other authors [ 4 ]. Rickard et al [ 26 ] visualized the umbilical cord already on the 23rd day of pregnancy, while Kumar et al [ 34 ] identified free movement of the umbilical cord on the 39th day of pregnancy.…”
Section: Discussionsupporting
confidence: 90%
“…In the umbilical artery, peak systolic velocity increased as pregnancy progressed and this pattern was also found in other studies in sheep [ 3 , 35 37 ]. In this study, as pregnancy progressed, the resistance and pulsatility indices decreased, which was also observed in other studies in sheep [ 3 , 4 , 36 – 38 ]. The end diastolic velocity was undetectable during the initial stages of pregnancy, while a gradual and progressive increase in this parameter was recorded from day 55 to the end of pregnancy.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations